1974
DOI: 10.1111/j.1471-0528.1974.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diameter of the Uterine Isthmus During the Menstrual Cycle, Pregnancy and the Puerperium

Abstract: Summary The diameter of the uterine isthmus was measured in 188 patients under different physiological conditions. It was found that measurements were reproducible with a low mean coefficient of variation (3 per cent). In the non‐pregnant patient the highest measurements were recorded during the menstrual period and the lowest in the preceding week. The isthmic diameter increased during the first trimester of pregnancy when it was slightly greater in parous than in nulliparous patients. Even 9 to 12 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that dilatation for induced abortion may cause remaining alterations of the internal os of the cervix. Johnstone et al [21 ] found a more dilated cervix at a six-week follow-up in patients dilated to more than 10 mm, than in patients less dilated; and Bergman and Svennerud [22], using a trac tion test, showed that patients with a history of consecu tive abortions had a wider internal cervical os than patients with full-time pregnancies. A wide cervical canal has also been associated with the clinical diagnosis of cer vical incompetence [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that dilatation for induced abortion may cause remaining alterations of the internal os of the cervix. Johnstone et al [21 ] found a more dilated cervix at a six-week follow-up in patients dilated to more than 10 mm, than in patients less dilated; and Bergman and Svennerud [22], using a trac tion test, showed that patients with a history of consecu tive abortions had a wider internal cervical os than patients with full-time pregnancies. A wide cervical canal has also been associated with the clinical diagnosis of cer vical incompetence [23,24].…”
Section: Discussionmentioning
confidence: 99%